Efektivitas Core Stability Exercise terhadap Pasien Low Back Pain Kronis : Literature Review - Wahyuni Wahyuni; Serina Laurenza Putri Rianto (Lembaga Pengembangan Kinerja Dosen, 2025)
Background: Low back pain (LBP) is one of the most common musculoskeletal problems that affect the quality of life and productivity of individuals. LBP lasting more than 12 weeks is categorized as chronic LBP and often has no specific cause. Core stability exercise (CSE) is one of the effective rehabilitation methods in managing pain and disability in chronic LBP patients. Objective: This review aims to evaluate the effectiveness of CSE in reducing pain in patients with chronic LBP based on a literature review. Methods: This study used the literature review method by reviewing various relevant studies related to CSE and chronic LBP. Data sources were obtained from databases such as PubMed, ScienceDirect, Google Scholar, and PEDro. Articles used had inclusion criteria in the form of randomized controlled trial (RCT) studies published in the last 10 years (2014-2024), in English, and involving patients with non-specific chronic LBP. Article quality assessment was conducted using the PEDro scale. Results: From the analysis of eight articles that met the inclusion criteria, it was found that CSE has significant effectiveness in reducing pain in patients with chronic LBP. The mean visual analogue scale (VAS) score showed a greater reduction in the group undergoing CSE compared to the control group or other therapeutic methods. Moreover, the combination of CSE with adjunctive therapies such as pain neuroscience education (PNE), interferential therapy (IFC), and myofascial release technique (MRT) showed better results in reducing pain and improving postural stability and physical function. Conclusion: CSE can be an effective rehabilitation method to reduce pain and improve core muscle stability in patients with chronic LBP. Combination with other therapies may provide more optimal results.